Systematic review about methods of energy expenditure and energy intake in children and adolescents - Deivis Elton Schilickmann Frainer; Fernando Adami; Francisco de Assis Guedes de Vasconcelos (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p197 The objective of this systematic review was to identify, describe and analyze methods used for determining energy expenditure and energy intake in clinical and population-based epidemiological studies. The study population was made up of children and adolescents aged from 6 to 18 years. The articles were identifi ed by means of searching the Medline database. A total of 141 articles were identifi ed, 32 of which were selected. From these, 10 articles were chosen, 6 of which were clinical epidemiological studies and 4 were populational epidemiological studies. The methods used to determine energy expenditure in the clinical studies were doubly labeled water and indirect calorimetry. In the populational studies, questionnaires on physical activity were used to determine the energy expended during physical activity. The methods used to evaluate nutritional intake, both in the clinical and populational epidemiological studies, were 24-hour dietary recalls, food records and food frequency questionnaires. The review goes on to discuss questions such as the manner in which these methods are employed and their validation and adaptation for populations of children and adolescents. It is concluded that care must be taken with the methodological aspects of epidemiological study design in order to avoid introducing bias to results and limiting conclusions.